Balancing Justice and Welfare Needs in Family Group Conferences for Children with Harmful Sexual Behavior: The HSB-FGC Framework. Issue 5 (4th July 2018) - Anderson, Monique; Parkinson, Kate
ABSTRACT: In England and Wales, family group conferences (FGCs) are most often found either in the field of youth justice or in the field of child protection, and consequently often have priorities in line with either one of the two systems. On the one hand, FGCs are a restorative justice tool to address offending behavior and hold young perpetrators to account, while giving victims the possibility of contributing to the justice process. On the other hand, FGCs address safeguarding concerns and are used to plan for child safety and protection. In cases where a young person has sexually harmed another young person, that is, has perpetrated harmful sexual behavior (HSB), all young people involved will have both justice and welfare needs. FGCs are emerging as promising mechanisms in such cases, not only because of their ability to deal with both sets of needs for both young people but also because of their potential to address more holistic needs. However, HSB cases are often complex and sensitive, and are not without risk. Drawing on their experiences in research and practice, the authors explore how the holistic needs of both the harmed and harming individual can be balanced within a risk managed HSB-FGC framework.